Development of a GIS Based Decision Support System for Spatial Planning and Management of Mining Natural Resources in West Kalimantan - sumbung, dwi yolanda (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This research aims to develop a Decision Support System (SPK) based on Geographic Information System (GIS) for the management of mining Natural Resources (SDA) in West Kalimantan. The region has abundant natural resources, but mining activities often result in serious environmental damage and trigger social conflicts. Therefore, a system is needed that can optimize spatial planning and natural resource management more efficiently and sustainably. For further research, it is recommended to conduct field testing of these systems with more complete data, as well as develop more sophisticated systems by utilizing the latest technologies, such as real-time data integration and AI-based analytics. This research can be expanded to include other mining areas in Indonesia, as well as deepening the more complex social and environmental impacts. Overall, this GIS-based SPK not only offers technical solutions in the management of mining natural resources but also has the potential to be a tool that can increase transparency, accountability, and community participation in mining-related decision-making. This research identifies the main components that must be present in the SPK, such as geospatial data integration, environmental impact analysis modeling, and social risk analysis features. The results of the study show that GIS-based SPK can increase the effectiveness of decision-making in the management of mining natural resources, help reduce environmental damage, and minimize negative social impacts, thereby supporting the achievement of sustainable development in West Kalimantan.